'Make the Connection' parenting skills programme: a controlled trial of associated improvement in maternal attitudes. (20th October 2018) - O'Neill, Amy; Swigger, Kimberly; Kuhlmeier, Valerie
ABSTRACT: Objective : Assess the effectiveness of Make the Connection (MTC), an attachment-focused parenting programme, in fostering maternal attitudes thought to underlie sensitive responding. Background : Effective parenting programmes are likely to mitigate negative outcomes associated with insecure attachment in infancy. Negative maternal attitudes and cognitions are thought to underlie insensitive parenting behaviour, and thus constitute a promising target for intervention. Methods : 180 mothers of young infants were assigned to experimental or waitlist control groups based on programme availability. Mothers completed questionnaires assessing parental attitudes at baseline, and again either after participating in MTC or after a 9-week waitlist period. Results : Participants who completed MTC showed significant improvement in overall attitude with a medium effect size relative to the waitlist control group, which showed no change. A small but significant interaction with infant age was noted, such that mothers of younger infants showed slightly more attitude improvement. Relative to the control group, participation in Make the Connection was associated with significant improvement in all attitudes except for self-efficacy as a parent, which improved with time regardless of programme participation. Conclusion : Make the Connection is effective in promoting positive parent-to-infant attachment and is a strong candidate for public health initiatives targeting parenting skills.